TELE OPERATED VEHICLE FOR THE MEASUREMENT OF ENVIRONMENTAL VARIABLES - Hernández Eskenazi, Abel; Herrera Martínez, Josué Daniel; García Mesa, Raydel (Telemática, 2021)
The design and construction of teleoperated vehicles constitute a current tendency in the development of telecommunications and the electronic. One of its main applications consists in the acquisition of data from the environment for its later study or its analysis in real-time. This document has as objective to expose the results of the construction of a teleoperated vehicle by Bluetooth wireless communication, through an Android application in a smartphone, for the monitoring of environmental variables in remote places or of difficult access for the human beings. Moreover, carried out the installation of a camera which by means of a connection by Wi-Fi (Wireless Fidelity) with other smartphones or tablets, permits to witness images in High Definition from the vehicle. It carries out an analysis of the state of the art of the teleoperated vehicles at present, the technical specifications of the created device, the advantages and the limitations that possess the prototype, and the possible applications that the project can have at present and in the future.